/ THE ASSOCIATION OF COMMON GST POLYMORPHISMS WITH INFLAMMATORY AND MULTIORGAN IMPAIRMENT BIOMARKERS IN COVID-19 - Jerotić, Djurdja; Krunić, Ana (Medicinski podmladak, 2023)
Introduction: Due to the established role of oxidative stress in the pathophysiology of COVID-19, it has been proposed that inter-individual differences in patients’ clinical manifestations might be affected by variations in genes encoding antioxidant enzymes, such as glutathione S-transferases (GSTs).Aim: The aim of this study was to assess the association of polymorphisms in cytosolic GSTs (GSTA1 rs3957357,  GSTM3 rs1332018  and GSTP1 rs1695) with inflammatory parameters (leukocytes, lymphocytes, monocytes, CRP, fibrinogen, ferritin) and multiorgan impairment biomarkers (urea, creatinine, AST, ALT, LDH) in  COVID-19 patients at two time points.Materials and Methods: GSTM3, GSTA1 and GSTP1 genotypes were determined in 150 COVID-19 patients by appropriate PCR methods.  Results:  Inflammatory biomarkers (leukocytes, lymphocytes, monocytes) increased 7 days upon admission to the hospital (p
Keywords: COVID-19, oxidative stress, glutathione S-transferases, polymorphism